Proton exchange membrane and preparation method and application thereof

By using a proton exchange membrane with a microporous polytetrafluoroethylene reinforcement layer and a multi-layer perfluorosulfonic acid resin structure in the fuel cell, the problems of large material thickness, high cost and high resistance value in the prior art are solved, and more efficient oxygen transmission and conductivity are achieved.

CN119627136APending Publication Date: 2025-03-14FTXT ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311183918.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The perfluorosulfonic acid proton exchange membrane material used in existing fuel cells is relatively thick, resulting in increased oxygen transmission resistance, high cost and large resistance value.

Method used

Microporous polytetrafluoroethylene is used as the reinforcement layer, and a multi-layer proton exchange membrane is formed by immersing in a perfluorosulfonic acid resin solution with different EW values, and the thickness and conductivity of the membrane are optimized through hot pressing and leveling processes.

Benefits of technology

It effectively reduces the material thickness and cost of the proton exchange membrane, improves the conductivity and oxygen transmission efficiency of the membrane, and reduces the resistance value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627136A_ABST
    Figure CN119627136A_ABST
Patent Text Reader

Abstract

The invention provides a proton exchange membrane as well as a preparation method and application thereof. The proton exchange membrane comprises a first perfluorinated sulfonic acid resin layer, a microporous enhancement layer and a second perfluorinated sulfonic acid resin layer, first perfluorinated sulfonic acid resin layers are arranged on the two sides of the microporous reinforcing layer; a second perfluorinated sulfonic acid resin layer is further arranged on the surface of the first perfluorinated sulfonic acid resin layer on one side; wherein the EW value of the first perfluorinated sulfonic acid resin is 700 to 900; the EW value of the second perfluorinated sulfonic acid resin is 900 to 1100. The proton exchange membrane containing two different EW values is prepared, the proton exchange membrane with the corresponding water retention rate and conductivity can be directionally selected according to the use working condition, the thickness of the proton exchange membrane is reduced, the oxygen transmission resistance is reduced, and the resistance value is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a proton exchange membrane, a preparation method thereof, and applications thereof. Background Art

[0002] In fuel cell devices, the proton exchange membrane (PEM) is a core component of the fuel cell (PEMFC), playing a key role in transporting protons and isolating the anode and cathode fuel gases from each other. An ideal PEM has uniform thickness, good proton conductivity, and chemical stability.

[0003] Due to its unique chemical composition and structure, perfluorosulfonic acid proton exchange membranes not only have excellent proton conductivity, but also have much better stability and lifespan than non-fluorinated proton exchange membranes. Therefore, the proton exchange membrane currently widely used in proton exchange membrane fuel cells is mainly perfluorosulfonic acid proton exchange membranes. Research and commercial products are mainly prepared by solution film formation, in which perfluorosulfonic acid resin is cast or cast on both sides of the microporous reinforcement layer, and the membrane is formed after drying and removing the solvent. The traditional process coats perfluorosulfonic acid resin on both sides of microporous polytetrafluoroethylene, which requires a large amount of sulfonic acid resin and is costly. In addition, thicker proton exchange membrane materials significantly increase the oxygen transmission resistance, hindering oxygen from entering the reaction point.

[0004] CN101692487A discloses a method for preparing a low-permeability proton exchange membrane for fuel cells. This method uses a combination of ultrasonic impregnation and spraying to composite a perfluorosulfonic acid resin onto the surface of an expanded polytetrafluoroethylene (EPTFE) microporous membrane. Ultrasonic impregnation involves immersing the expanded polytetrafluoroethylene (EPTFE) microporous membrane in an ultrasonically vibrated perfluorosulfonic acid resin solution. Spraying involves repeatedly coating both sides of the ultrasonically impregnated expanded polytetrafluoroethylene (EPTFE) microporous membrane with a spray coating until the membrane reaches a predetermined thickness. This method, in order to achieve high electrochemical performance, requires a large amount of sulfonic acid resin, resulting in a high thickness of the entire proton exchange membrane material.

[0005] CN101276917A discloses a process for forming a composite proton exchange membrane for fuel cells, including attaching a perfluorosulfonic acid resin to an expanded polytetrafluoroethylene (EPTFE) microporous base membrane. The process comprises soaking the EPTFE microporous base membrane in a dilute perfluorosulfonic acid solution, spraying the perfluorosulfonic acid resin solution on both sides of the base membrane, and heat-setting the composite membrane. This method, in order to achieve high electrochemical performance, requires a large amount of sulfonic acid resin, resulting in a high thickness of the entire proton exchange membrane material.

[0006] In view of this, the present invention is proposed. Summary of the Invention

[0007] One of the purposes of the present invention is to provide a proton exchange membrane, comprising a first perfluorosulfonic acid resin layer, a microporous reinforcement layer, and a second perfluorosulfonic acid resin layer; the first perfluorosulfonic acid resin layer is disposed on both sides of the microporous reinforcement layer; wherein a second perfluorosulfonic acid resin layer is also disposed on the surface of the first perfluorosulfonic acid resin layer on one side; wherein the EW value of the first perfluorosulfonic acid resin is 700-900; and the EW value of the second perfluorosulfonic acid resin is independently 900-1100. The proton exchange membrane of the present invention can effectively reduce costs and material thickness; and a proton exchange membrane with two different EW values ​​can be prepared. The proton exchange membrane with corresponding water retention rate and conductivity can be selected according to the operating conditions, thereby reducing the thickness of the proton exchange membrane, reducing oxygen transmission resistance, and reducing the electrical resistance value.

[0008] A second objective of the present invention is to provide a method for preparing the aforementioned proton exchange membrane, comprising the following steps: immersing the microporous reinforcement layer in a first perfluorosulfonic acid resin solution to allow absorption and microswelling; coating the surface of one side of the first perfluorosulfonic acid resin layer with a second perfluorosulfonic acid resin solution; sequentially performing a first drying step, leveling, and a second drying step; and hot pressing to obtain the aforementioned proton exchange membrane. This method allows for the targeted selection of a proton exchange membrane with appropriate water retention and conductivity based on operating conditions, thereby reducing the thickness of the proton exchange membrane, lowering oxygen transmission resistance, and lowering electrical resistance.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0010] In a first aspect, the present invention provides a proton exchange membrane, comprising a first perfluorosulfonic acid resin layer, a microporous reinforcement layer, and a second perfluorosulfonic acid resin layer; the first perfluorosulfonic acid resin layer is provided on both sides of the microporous reinforcement layer; wherein the second perfluorosulfonic acid resin layer is further provided on the surface of the first perfluorosulfonic acid resin layer on one side;

[0011] The EW value of the first perfluorosulfonic acid resin is 700-900, for example, 700, 720, 740, 760, 780, 900, etc., and the EW value of the second perfluorosulfonic acid resin is 900-1100, for example, 900, 920, 940, 960, 980, 1000, 1020, 1040, 1060, 1080, 1100, etc.

[0012] In the present invention, a proton exchange membrane is obtained by coating perfluorosulfonic acid resin solutions with different EW value ranges on both sides of a microporous reinforcement layer. This method can prepare a proton exchange membrane containing two different EW values. The proton exchange membrane with corresponding water retention rate and conductivity can be selected according to the operating conditions, thereby reducing the thickness of the proton exchange membrane, reducing the oxygen transmission resistance, and reducing the resistance value.

[0013] Preferably, the thickness of the first perfluorosulfonic acid resin layer is 1-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0014] Preferably, the thickness of the second perfluorosulfonic acid resin layer is 5-20 μm, for example, 15 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.

[0015] Preferably, the microporous reinforcement layer is a porous polytetrafluoroethylene (e-PTFE) film layer.

[0016] Preferably, the thickness of the porous polytetrafluoroethylene film layer is 3-80 μm, for example, 3 μm, 4 μm, 6 μm, 8 μm, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, etc.

[0017] Preferably, the pore size of the porous polytetrafluoroethylene film layer is 2-30 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 20 μm, 30 μm, etc.

[0018] Preferably, the porosity of the porous polytetrafluoroethylene film layer is 30-80%, for example, it can be 30%, 40%, 50%, 60%, 70%, 80%, etc.

[0019] In a second aspect, the present invention provides a method for preparing a proton exchange membrane as described in the first aspect, the preparation method comprising the following steps:

[0020] The microporous reinforcement layer is immersed in a first perfluorosulfonic acid resin solution to absorb and slightly swell; a second perfluorosulfonic acid resin solution is then coated on the surface of the first perfluorosulfonic acid resin layer on one side, and a first drying, leveling, and second drying process are performed in sequence; and hot pressing is performed to obtain the proton exchange membrane.

[0021] In the present invention, a proton exchange membrane with a small amount of resin on both sides is obtained by soaking microporous polytetrafluoroethylene in an electrolyte resin. A perfluorosulfonic acid resin solution with different EW values ​​is then coated on one side, effectively reducing costs and material thickness. A leveling process is also added, in which a mixture of alcohol and water is sprayed on the surface of the electrolyte resin layer to level and dry the resin layer. This effectively improves the surface flatness of the proton exchange membrane and helps reduce the contact resistance between the proton membrane and the catalyst layer.

[0022] Preferably, the solid content of the first perfluorosulfonic acid resin solution and the second perfluorosulfonic acid resin solution is independently 5-50%, for example, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0023] Preferably, the soaking temperature is 10-30°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, etc., and the soaking time is 12-24h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h, etc.

[0024] Preferably, the temperature of the first drying and the second drying is independently 50-70°C, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc.

[0025] Preferably, the first drying time is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, etc.

[0026] Preferably, the first drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 vol%, for example, 5 vol%, 4 vol%, 3 vol%, 2 vol%, 1 vol%, etc.

[0027] Preferably, the second drying time is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, etc.

[0028] Preferably, the second drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 vol%, for example, 5 vol%, 4 vol%, 3 vol%, 2 vol%, 1 vol%, etc.

[0029] Preferably, the leveling method includes the following steps: spraying an alcohol-water mixture onto the surface of the perfluorosulfonic acid resin layer formed after the first drying.

[0030] Preferably, the volume ratio of alcohol to water in the alcohol-water mixture is (0.5-1):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.

[0031] Preferably, the alcohol in the alcohol-water mixture is selected from C1-C5 (for example, C1, C2, C3, C4, C5) straight-chain or branched alkyl alcohol, for example, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, etc., preferably ethanol and / or n-propanol, more preferably ethanol.

[0032] Preferably, the spraying density is 0.5-0.8 mL / cm 2 , for example, it can be 0.5mL / cm 2 , 0.55mL / cm 2 , 0.6mL / cm 2 , 0.65mL / cm 2 , 0.7mL / cm 2 , 0.75mL / cm 2 , 0.8mL / cm 2 wait.

[0033] Preferably, the hot pressing temperature is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc., and the hot pressing pressure is 1-10MPa, for example, it can be 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, etc.

[0034] As a preferred technical solution of the present invention, the method for preparing the proton exchange membrane comprises the following steps:

[0035] S1 Preparation of a first perfluorosulfonic acid resin layer: Immerse a porous polytetrafluoroethylene film in a first perfluorosulfonic acid resin solution having an EW value of 600-800 for 12-24 hours to allow absorption and slight swelling to form a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0036] S2: Preparation of the second perfluorosulfonic acid resin layer: Coating the second perfluorosulfonic acid resin solution on the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1, performing a first drying, then spraying the surface of the second perfluorosulfonic acid resin layer with an alcohol-water mixture having a volume ratio of alcohol to water of (0.5-1):1 to level it, and finally performing a second drying;

[0037] S3 hot pressing: hot pressing the composite membrane obtained in S2 at 80-150° C. and a pressure of 1-10 MPa to obtain the proton exchange membrane.

[0038] In a third aspect, the present invention provides a use of the proton exchange membrane as described in the first aspect in preparing a fuel cell.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention uses microporous polytetrafluoroethylene soaked in electrolyte resin to obtain a proton exchange membrane with a small amount of resin on both sides, and then coats one side with a perfluorosulfonic acid resin solution with different EW values, which can effectively reduce costs and reduce material thickness;

[0041] (2) The present invention prepares a proton exchange membrane with two different EW values. The proton exchange membrane with corresponding water retention rate and conductivity can be selected according to the operating conditions, thereby reducing the thickness of the proton exchange membrane, reducing the oxygen transmission resistance, and reducing the resistance value. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 Schematic diagram of the structure of the proton exchange membrane of the present invention.

[0044] Among them, 1 is a microporous reinforcement layer, 2 is a first perfluorosulfonic acid resin layer, and 3 is a second perfluorosulfonic acid resin layer. DETAILED DESCRIPTION

[0045] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear; however, in the event of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, the use of "or" means "and / or" unless otherwise stated. In addition, the use of the term "including" and other forms is non-limiting.

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.

[0047] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention as claimed, but rather merely represents selected embodiments of the present invention. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort shall fall within the scope of protection of the present invention.

[0048] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, it does not need to be further defined or explained in subsequent drawings.

[0049] In the description of the present invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer" and the like indicate positions or locations based on the positions shown in the accompanying drawings, or the positions or locations in which the inventive product is typically placed when in use. These terms are intended solely to facilitate the description of the present invention and to simplify the description, and are not intended to indicate or imply that the devices or components referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limitations on the present invention. Furthermore, the terms "first," "second," and "third," etc., are used solely to distinguish descriptions and should not be construed as indicating or implying relative importance.

[0050] Furthermore, terms such as "horizontal," "vertical," and "overhanging" do not necessarily imply that a component must be absolutely horizontal or overhanging, but rather that it can be slightly tilted. For example, "horizontal" simply means that its direction is more horizontal than "vertical," and does not mean that the structure must be completely horizontal, but rather that it can be slightly tilted.

[0051] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0052] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0053] Example 1

[0054] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0055] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0056] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1 on the surface, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0057] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0058] Example 2

[0059] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0060] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0061] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 1000, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying the surface with an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0062] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0063] Example 3

[0064] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0065] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0066] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 1100, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying the surface with an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0067] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0068] Example 4

[0069] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0070] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0071] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1 on the surface, and drying again at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%;

[0072] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0073] Example 5

[0074] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0075] S1 selects a 10 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 5% and an EW value of 720, and soaks it at room temperature for 18 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0076] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 5% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1 on the surface, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0077] S3 puts the above sample into a hot press at a temperature of 80° C. and a pressure of 8 MPa to obtain a proton exchange membrane with a composite structure after hot pressing.

[0078] Example 6

[0079] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0080] S1 selects a 30 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 20% and an EW value of 720, and soaks it at room temperature for 24 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0081] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 20% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1 on the surface, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0082] S3 puts the above sample into a hot press at a temperature of 150° C. and a pressure of 2 MPa to obtain a composite proton exchange membrane after hot pressing.

[0083] Example 7

[0084] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0085] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0086] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.5:1 on the surface, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0087] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0088] Example 8

[0089] This embodiment provides a proton exchange membrane, which is prepared by the following method:

[0090] S1 selects a 20 μm e-PTFE film (pore size of 10 μm, porosity of 70%), places it in a first perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, and soaks it at room temperature for 12 hours to absorb and slightly swell, forming a first perfluorosulfonic acid resin layer on both sides of the porous polytetrafluoroethylene film;

[0091] S2: coating the surface of the first perfluorosulfonic acid resin layer on one side of the composite membrane obtained in S1 with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 900, with a wet film thickness of 100 μm, drying at 60° C. for 20 min until the liquid content is reduced to less than 5 vol%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 1:1 on the surface, and drying again at 60° C. for 15 min until the liquid content is reduced to less than 5 vol%;

[0092] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0093] Comparative Example 1

[0094] This comparative example provides a proton exchange membrane, which is prepared by the following method:

[0095] S1 uses a 20μm e-PTFE film (pore size of 10μm, porosity of 70%), and coats one side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900. The wet film thickness is 100μm. After drying at 60°C for 20min until the liquid content drops below 5vol%, the surface is sprayed with an ethanol-water mixture with a volume ratio of 0.6:1, and then dried at 60°C for 15min until the liquid content drops below 5vol%.

[0096] S2 is coated on the other side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900, with a wet film thickness of 100 μm, and dried at 60°C for 20 minutes until the liquid content drops below 5 vol%, and then sprayed with an ethanol-water mixture with a volume ratio of 0.6:1 on the surface, and then dried at 60°C for 15 minutes until the liquid content drops below 5 vol%;

[0097] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0098] Comparative Example 2

[0099] This comparative example provides a proton exchange membrane, which is prepared by the following method:

[0100] S1 uses a 20μm e-PTFE film (pore size of 10μm, porosity of 70%), and coats one side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 600. The wet film thickness is 100μm. After drying at 60°C for 20min until the liquid content drops below 5vol%, the surface is sprayed with an ethanol-water mixture with a volume ratio of 0.6:1, and then dried at 60°C for 15min until the liquid content drops below 5vol%.

[0101] S2 is coated on the other side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 1500, with a wet film thickness of 100 μm, and dried at 60°C for 20 minutes until the liquid content drops below 5 vol%, and then sprayed with an ethanol-water mixture with a volume ratio of 0.6:1 on the surface, and then dried at 60°C for 15 minutes until the liquid content drops below 5 vol%;

[0102] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0103] Comparative Example 3

[0104] This comparative example provides a proton exchange membrane, which is prepared by the following method:

[0105] S1 uses a 20μm e-PTFE film (pore size of 10μm, porosity of 70%), and coats one side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900. The wet film thickness is 100μm. After drying at 60°C for 20min until the liquid content drops below 5vol%, the surface is sprayed with an ethanol-water mixture with a volume ratio of 0.6:1, and then dried at 60°C for 15min until the liquid content drops below 5vol%.

[0106] S2 is coated on the other side with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm, and dried at 60°C for 20 minutes until the liquid content drops below 5 vol%, and then sprayed with an ethanol-water mixture with a volume ratio of 0.6:1 on the surface, and then dried at 60°C for 15 minutes until the liquid content drops below 5 vol%;

[0107] S3 puts the above sample into a hot press at a temperature of 90° C. and a pressure of 5 MPa to obtain a composite proton exchange membrane after hot pressing.

[0108] Test Example 1

[0109] Test samples: proton exchange membranes provided in Examples 1-8 and proton exchange membranes provided in Comparative Examples 1-3;

[0110] Test method:

[0111] (1) Exchange membrane thickness: measured using a thickness gauge;

[0112] (2) Proton conductivity: using the two-electrode AC impedance method, at 1HZ-10 5 In the HZ frequency range, the impedance of the membrane is measured and the proton conductivity of the membrane is obtained by calculation;

[0113] The specific test results are shown in Table 1 below:

[0114] Table 1

[0115]

[0116]

[0117] As shown in Table 1, the present invention utilizes microporous polytetrafluoroethylene soaked in an electrolyte resin to create a proton exchange membrane with a small amount of resin on both sides. This membrane is then coated on one side with a perfluorosulfonic acid resin solution of varying EW values. This effectively reduces costs, reduces material thickness to below 24.5 μm, and increases proton conductivity to above 0.045 S / cm. This demonstrates that the present invention produces a proton exchange membrane with two different EW values, enabling the targeted selection of a proton exchange membrane with appropriate water retention and conductivity based on operating conditions. This reduces membrane thickness, oxygen transport resistance, and electrical resistance.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A proton exchange membrane, characterized in that: The proton exchange membrane comprises a first perfluorosulfonic acid resin layer, a microporous reinforcement layer and a second perfluorosulfonic acid resin layer; the first perfluorosulfonic acid resin layer is disposed on both sides of the microporous reinforcement layer; wherein the second perfluorosulfonic acid resin layer is also disposed on the surface of the first perfluorosulfonic acid resin layer on one side; Wherein, the EW value of the first perfluorosulfonic acid resin is 700-900; and the EW value of the second perfluorosulfonic acid resin is 900-1100.

2. The proton exchange membrane according to claim 1, characterized in that The thickness of the first perfluorosulfonic acid resin layer is 1-10 μm.

3. The proton exchange membrane according to claim 1, characterized in that The thickness of the second perfluorosulfonic acid resin layer is 5-20 μm.

4. The proton exchange membrane according to claim 1, characterized in that The microporous reinforcement layer is a porous polytetrafluoroethylene film layer; Preferably, the thickness of the porous polytetrafluoroethylene film layer is 3-80 μm; Preferably, the pore size of the porous polytetrafluoroethylene film layer is 2-30 μm; Preferably, the porosity of the porous polytetrafluoroethylene film layer is 30-80%.

5. A method for preparing a proton exchange membrane according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The microporous reinforcement layer is immersed in the first perfluorosulfonic acid resin solution to absorb and slightly swell; the second perfluorosulfonic acid resin solution is then coated on the surface of the first perfluorosulfonic acid resin layer on one side, and the first drying-leveling-second drying are performed in sequence; hot pressing is performed; and the proton exchange membrane is obtained.

6. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The solid content of the first perfluorosulfonic acid resin solution and the second perfluorosulfonic acid resin solution is independently 5-50%.

7. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The soaking temperature is 10-30°C, and the soaking time is 12-24h.

8. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The temperatures of the first drying and the second drying are independently 50-70°C; Preferably, the first drying time is 10-30 min; Preferably, the first drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 vol%; Preferably, the second drying time is 10-30 minutes; Preferably, the second drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 vol%.

9. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The leveling method comprises the following steps: spraying a mixture of alcohol and water onto the surface of the perfluorosulfonic acid resin layer formed after the first drying; Preferably, the volume ratio of alcohol to water in the alcohol-water mixture is (0.5-1):1; Preferably, the alcohol in the alcohol-water mixture is selected from C1-C5 straight-chain or branched alkyl alcohol, preferably ethanol and / or n-propanol, and more preferably ethanol; Preferably, the spraying density is 0.5-0.8 mL / cm 2 ; Preferably, the hot pressing temperature is 80-150° C., and the hot pressing pressure is 1-10 MPa.

10. Use of the proton exchange membrane according to any one of claims 1 to 4 in the preparation of a fuel cell.

Citation Information

Patent Citations

  • Technique for shaping composite proton exchange membrane for fuel cell

    CN101276917A

  • Method for preparing low-permeability proton exchange membrane for fuel cell

    CN101692487A